A reductive interpretation of Climate-Smart Agriculture limits its positive effects - Pinto, Alex de (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Presentation by Alex De Pinto, International Food Policy Research Institute (IFPRI) International conference on agricultural emissions and food security: Connecting research to policy and practice 10-13 September 2018 Berlin, Germany